2011
DOI: 10.3390/insects2020173
|View full text |Cite
|
Sign up to set email alerts
|

Population Growth Potential of the Bed Bug, Cimex lectularius L.: A Life Table Analysis

Abstract: Experimental life tables were constructed and analyzed for three strains of the common bed bug: a pyrethroid-susceptible laboratory strain (HS), a highly resistant field strain (RR), and a field strain with a declining level of resistance (KR). Egg to adult survival in the RR strain was 94% compared with 79% and 69% in the HS and KR strains, respectively. The RR strain also developed significantly faster from egg to adult (∼35 days) than the other two strains (∼40 days). Analysis of a survivorship and fecundit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 35 publications
1
33
0
Order By: Relevance
“…The results of this study conform to other studies on bed bug field strains (both C. lectularius and C. hemipterus ) in reinforcing a trend of pyrethroid resistance being widespread (Yoon et al ; Seong et al ; Zhu et al ; Tawatsin et al ; Durand et al ; Palenchar et al ) and present at an extent that could compromise the insecticide efficacy of some formulations (Boase et al ; Moore and Miller ; Moore and Miller ; Polanco et al ; Gordon et al ), although we have found that aerosol‐based pyrethroids are still effective at killing even the most resistant strain when applied directly at the insect (Lilly and Doggett, unpublished). Furthermore, the results of imidacloprid topical discriminating dose assays against C. lectularius support the findings of the singular study to date, which determined via a similar topical methodology that resistance had developed (to varying degrees) in three field strains from the U.S. (Romero and Anderson ).…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study conform to other studies on bed bug field strains (both C. lectularius and C. hemipterus ) in reinforcing a trend of pyrethroid resistance being widespread (Yoon et al ; Seong et al ; Zhu et al ; Tawatsin et al ; Durand et al ; Palenchar et al ) and present at an extent that could compromise the insecticide efficacy of some formulations (Boase et al ; Moore and Miller ; Moore and Miller ; Polanco et al ; Gordon et al ), although we have found that aerosol‐based pyrethroids are still effective at killing even the most resistant strain when applied directly at the insect (Lilly and Doggett, unpublished). Furthermore, the results of imidacloprid topical discriminating dose assays against C. lectularius support the findings of the singular study to date, which determined via a similar topical methodology that resistance had developed (to varying degrees) in three field strains from the U.S. (Romero and Anderson ).…”
Section: Discussionsupporting
confidence: 91%
“…In the highly resistant (B‐haplotype) Richmond field strain of C. lectularius , which has been documented as having large numbers of upregulated genes coding for detoxification enzymes (Adelman et al , 2011; Polanco et al , 2011a), egg‐to‐adult survival was significantly higher and egg‐to‐adult developmental rates were demonstrated to be significantly faster than for a susceptible laboratory reference strain. Overall, under optimal conditions the resistant strain demonstrated the potential for a 35‐fold increase in population density per generation over the susceptible strain (Polanco et al , 2011a). However, the Richmond strain was also found to be much more vulnerable to mortality during starvation than susceptible bed bugs.…”
Section: Fitness Advantages or Costs Associated With Pyrethroid Resismentioning
confidence: 99%
“…This method has only rarely been used (Stiefel et al. 1992, 1997; Polanco et al. 2011), but was selected because there was evidence of an unquantifiable underestimation of population size at early instars (see fig.…”
Section: Methodsmentioning
confidence: 99%